Immune-Mediated Autonomic Neuropathies following Allogeneic Stem Cell Transplantation in Acute Myeloid Leukemia. (27th August 2017) - Mangaonkar, Abhishek; Khateeb, Hassan Al; Duma, Narjust; Louis, Erik K. St.; McKeon, Andrew; Patnaik, Mrinal; Hogan, William; Litzow, Mark; Kourelis, Taxiarchis
Abstract : Background/Aims . Autonomic dysfunction (AD) after allogeneic stem cell transplant (SCT) is a rare occurrence and likely immune-mediated in etiology. There is limited literature on this topic and hence, we wish to briefly describe management of two cases at our institution and their outcomes. Methods . We retrospectively identified two patients with immune-mediated AD after SCT from our database. Immune-mediated AD was defined as AD secondary to an immune-mediated etiology without an alternative cause and responding to immunosuppression. Results . The first case is of a 32-year-old man with acute myeloid leukemia (AML) who underwent double umbilical cord allogeneic SCT. The second patient was a 51-year-old woman with secondary AML who underwent matched-related donor allogeneic SCT. Both underwent an extensive work-up for an underlying etiology prior to treatment with intravenous immunoglobulin (IVIG). Conclusions . AD after SCT is a rare yet significant clinical entity. A work-up of underlying etiology should be performed. IVIG is a treatment option for these patients.